IMPLEMENTASI KEBIJAKAN PROGRAM PEMBERDAYAAN MASYARAKAT DALAM MANAJEMEN KONFLIK DI DISTRIK SUGAPA KABUPATEN INTAN JAYA - Iga Putra Amalo; Nur Aedah (Universitas Cenderawasih, 2022)
The purpose of this study is to accelerate poverty alleviation and provide opportunities for the community to be able to open their own jobs so that they can develop development and empower communities in the village to develop and not be left behind. Types of Descriptive-Qualitative Research, Data were collected using techniques in the form of observation, documentation and developed by interviewing the informants. The data was analyzed descriptively qualitatively, namely analyzing all the data that the author had collected, both primary data and secondary data and then presented in the form of informants obtained from interviews and interview guidelines. From the results of the study it was found that the implementation of community empowerment program policies in conflict management in the Sugapa district of Intan Jaya district were: (a) communication in the socialization of the Community Empowerment Program (PRODAMAS) was also still not going well. (b) Resources in the realization of Prodamas funds in each RT are still focused on development (c) There are still some dispositions that have not carried out citizen consultations (d) the bureaucratic structure is good, where technical instructions in the implementation of community empowerment programs have gone well.